2020
DOI: 10.1177/0003134820973356
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Impact of COVID-19 Pandemic on Racial and Ethnic Minorities

Abstract: Background Health disparities are prevalent in many areas of medicine. We aimed to investigate the impact of the COVID-19 pandemic on racial/ethnic groups in the United States (US) and to assess the effects of social distancing, social vulnerability metrics, and medical disparities. Methods A cross-sectional study was conducted utilizing data from the COVID-19 Tracking Project and the Centers for Disease Control and Prevention (CDC). Demographic data were obtained from the US Census Bureau, social vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 11 publications
2
122
0
Order By: Relevance
“…The importance of direct age standardization in examining racial/ethnic disparities in COVID-19 mortality is illustrated by a comparison of our estimate of the Black-White death rate ratio in Minnesota (3.2) to that in previous studies. Two studies that relied upon crude death rates reported ratios of 1.45 [40] and 1.7 [38], and one study that relied upon indirectly age-adjusted death rates reported a ratio of 1.4 [39]. The COVID Racial Data Tracker (as of February 2021), which relies upon crude death rate estimates, reported no racial/ ethnic disparity between non-Hispanic Black and non-Hispanic White COVID-19 mortality rates in Minnesota [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of direct age standardization in examining racial/ethnic disparities in COVID-19 mortality is illustrated by a comparison of our estimate of the Black-White death rate ratio in Minnesota (3.2) to that in previous studies. Two studies that relied upon crude death rates reported ratios of 1.45 [40] and 1.7 [38], and one study that relied upon indirectly age-adjusted death rates reported a ratio of 1.4 [39]. The COVID Racial Data Tracker (as of February 2021), which relies upon crude death rate estimates, reported no racial/ ethnic disparity between non-Hispanic Black and non-Hispanic White COVID-19 mortality rates in Minnesota [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have examined racial disparities in COVID-19 mortality using crude death rates [35][36][37][38]. Two studies reported national, race-specific COVID-19 mortality rates without age adjustment [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lower income levels were associated with loneliness in our sample, overall the patients were White, well-educated, and reported an annual income of >$60,000. Given the racial/ethnic disparities associated with the COVID-19 pandemic, [40][41][42] future studies need to evaluate the relationships between loneliness and additional social determinants of health (eg, availability of technology and level of interpersonal and community violence) among both socioeconomically advantaged and socioeconomically disadvantaged individuals. Given the lack of information on the total number of patients who received the survey, as well as Cancer Month 0, 2021 on the characteristics of the patients who chose not to complete the survey, our findings may not generalize to all patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results varied slightly from other studies. Another study found the Northeast exhibited the largest CFR (5.9%), then the Midwest (5.6%), West (5.1%) and South (5.05%) [ 28 ]. One possible explanation of this inconsistency is the ZCs representing the West region reside within metropolitan areas, where larger population densities can facilitate increased spread and elevated CFRs.…”
Section: Discussionmentioning
confidence: 99%